Effect of Pseuduvaria macrophylla in attenuating hyperglycemia mediated oxidative stress and inflammatory response in STZ-nicotinamide induced diabetic rats by upregulating insulin secretion and glucose transporter-1, 2 and 4 proteins expression - Taha H.; Arya A.; Khan A.K.; Shahid N.; Noordin M.I.B.; Mohan S. (University of South Bohemia, 2023)
antidiabetic agent; C peptide; glibenclamide; glucose; glucose transporter 1; glucose transporter 2; glucose transporter 4; glutathione; insulin; interleukin 1beta; interleukin 6; nicotinamide; plant extract; Pseuduvaria macrophylla extract; transforming growth factor beta1; tumor necrosis factor; unclassified drug; animal cell; animal experiment; animal model; animal tissue; Annonaceae; antidiabetic activity; Article; body weight; controlled study; glucose blood level; histopathology; immunohistochemistry; inflammation; insulin blood level; insulin level; insulin release; insulin signaling; lipid peroxidation; non insulin dependent diabetes mellitus; nonhuman; oxidative stress; pancreas islet; pancreas islet beta cell; pancreas tissue; peroxidation; protein expression; Pseuduvaria macrophylla; rat; toxicity testing